2012
DOI: 10.1371/journal.pone.0032400
|View full text |Cite
|
Sign up to set email alerts
|

Immune Responses in Pigs Vaccinated with Adjuvanted and Non-Adjuvanted A(H1N1)pdm/09 Influenza Vaccines Used in Human Immunization Programmes

Abstract: Following the emergence and global spread of a novel H1N1 influenza virus in 2009, two A(H1N1)pdm/09 influenza vaccines produced from the A/California/07/09 H1N1 strain were selected and used for the national immunisation programme in the United Kingdom: an adjuvanted split virion vaccine and a non-adjuvanted whole virion vaccine. In this study, we assessed the immune responses generated in inbred large white pigs (Babraham line) following vaccination with these vaccines and after challenge with A(H1N1)pdm/09 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Pigs have also been used to test influenza vaccines 3 and have the advantage that there is no shortage of supply, reagents are available for T cell analysis, and they can be infected with viruses of many different subtypes as both α‐2,3‐ and α‐2,6‐galactose sialic acid linkages are present on cells lining the pig trachea, 4 which provides an opportunity to study heterosubtypic protection induced by vaccination. A recent comparison of pandemic H1N1 vaccines in pigs 5 produced data that were in close agreement with a similar study in humans, 6 providing further support for the greater use of this model in future. However all of these models have the disadvantage that they cannot mimic the complex immune memory to influenza A virus found in humans after a lifetime of repeated exposures, and the results of experimental studies must be interpreted with this in mind.…”
Section: Animal Models For Testing Candidate Influenza Vaccinessupporting
confidence: 72%
“…Pigs have also been used to test influenza vaccines 3 and have the advantage that there is no shortage of supply, reagents are available for T cell analysis, and they can be infected with viruses of many different subtypes as both α‐2,3‐ and α‐2,6‐galactose sialic acid linkages are present on cells lining the pig trachea, 4 which provides an opportunity to study heterosubtypic protection induced by vaccination. A recent comparison of pandemic H1N1 vaccines in pigs 5 produced data that were in close agreement with a similar study in humans, 6 providing further support for the greater use of this model in future. However all of these models have the disadvantage that they cannot mimic the complex immune memory to influenza A virus found in humans after a lifetime of repeated exposures, and the results of experimental studies must be interpreted with this in mind.…”
Section: Animal Models For Testing Candidate Influenza Vaccinessupporting
confidence: 72%
“…Results shown are the mean of all individuals in each of the groups ± standard deviation. Serum from pigs immunized with commercial A(H1N1)pdm09 vaccine Pandemrix (GSK) and challenged with A/England/195/09 (pdmH1N1) virus as previously described [ 11 ] was used as a positive control and gave a titer of 2048.…”
Section: Resultsmentioning
confidence: 99%
“…Influenza virus specific antibody (Ab) titres in serum and BAL fluid were determined by HAI using standard protocols [ 11 ]. Briefly, H1N1 HAI antibody titres were determined using 0.5% chicken red blood cells and A/Sw/Eng/1353/09 live antigen at a concentration of 4 HA units/mL.…”
Section: Methodsmentioning
confidence: 99%
“…A FLUAVsw-specific proliferation of lymphocytes isolated from blood has been reported following infection of pigs with H3N2 and H1N1 FLUAVsw strains [ 7 - 9 ]. One study demonstrated the proliferation of blood-derived CD4 + and CD8 + T cells following vaccination with a human pandemic H1N1 vaccine [ 10 ]. Also, the presence of H1N1-specific IFN-γ producing T cells in tracheobronchial lymph nodes, spleen and nasal mucosa has been described [ 5 ].…”
Section: Introductionmentioning
confidence: 99%